Structural and chemical relationships in metal phosphine complexes relevant to homogeneous catalysis - Ndula, Bungu Peter (University of the Free State, 2010)
The aim of this research work was to improve the fundamental understanding of the role selected tertiary bicyclic and conventional phosphine ligands play in modified cobalt-catalyzed hydroformylation. Selected bicyclic ligands were synthesized by radical addition of 1-alkenes to the 2° phosphines shown in Figure 1 (see in full text PDF). The following ligands were synthesized in this way: Phoban-Q (Q = CH2CH3 (C2), (CH2)4CH3 (Cs), (CH2)3N(CH3)2 (C3NMe2), Lim-Cs, VCH-Cs and PA-Cs. Phoban-Cy was made from the reaction between a diene and a 1° phosphine, H2PCy, with a radical initiator at 100°C. the second set ranging from PnBu3 to the Lim family with hydrogenation ranging from 9 - 15% respectively. Crystal structures of the cobalt dimers of the following ligands; Phoban[3.3.1]-C21 Phoban[3.3.1]-C5, Phoban[3.3.1]-C3NMe2, Phoban[3.3.1]-Cy, PA-C5, PCy3, and PCp3 were obtained and characterised by X-ray crystallography. A series of [Rh(acac)(CO)(P-Ph)] complexes where P-Ph = Phoban[3.3.1]-Ph, Phoban[4.2.1]-Ph, a mixture of 4R, 8S- and 4S, 8S-Lim-Ph, a mixture of VCH[3.3.1]-Ph and VCH[3.2.2]-Ph and PA-Ph were successfully synthesized and characterised by NMR and IR spectrophotometers. The crystal structures of [Rh(acac)(CO)(4R, BS-Lim-Ph)] and [Rh(acac)(CO)(PA-Ph)] were obtained and characterised by X-ray crystallography. The oxidative addition and CO-insertion reactions of the rhodium complexes of these ligands were carried out and the results indicate that the Lim-Ph systems were the most active among the bicyclic ligands included in the study. The general reactivity trend for the oxidative addition was found to be: 4S, 8S-Lim-Ph > 4R, 8S-Lim-Ph > VCH-Ph > Phoban[3.3.1]-Ph > Phoban[4.2.1]Ph> PPh3 - PCy3 >PA-Ph. The overall reactivity trend for the CO-insertion reaction was determined as 4S, 8S-Lim-Ph > 4R, 8S-Lim-Ph > Phoban[4.2.1]-Ph > VCH-Ph > Phoban[3.3.1]-Ph > PA-Ph.

Die doel van die navorsing was om die fundamentele begrip vir die rol wat geselekteerde tersiere bisikliese en konvensionele fosfien ligande in gemodifiseerde kobalt gekataliseerde hidroformilering speel te verbeter. Geselekteerde bisikliese ligande is gesintetiseer deur die radikaal addisie van 1-alkene aan die 2° fosfiene in Figuur 1 (sien in volteks PDF). Die volgende ligande is op die manier gesintetiseer: Phoban-Q (Q = CH2CH3 (C2), (CH2)4CH3 (C5), (CH2)3N(CH3)2 (C3NMe2), Lim-C5, VCH-C5 en PA-C5. Phoban-Cy is gemaak deur die reaksie tussen 'n dieen en 'n 1° fosfien, H2PCy, met 'n radikaal inisieerder by 100°C. groep en wissel van PnBu3 tot die Lim familie met hidroginering wat wissel van 9 - 15% onderskeidelik. Kristalstrukture van kobalt dimere van die volgende ligande Phoban[3.3.1]-C2, Phoban[3.3.1]-C5, Phoban[3.3.1]-C3NMe2, Phoban[3.3.1]-Cy, PA-C5, PCy3 en PCp3 is verkry en gekarakteriseer met X-straal kristallografie. 'n Reeks [Rh(acac)(CO)(P-Ph)] komplekse waar P-Ph = Phoban[3.3.1]-Ph, Phoban[4.2.1]-Ph, 'n mengsel van 4R, 8S- en 4S, 8S-Lim-Ph, 'n mengsel van VCH[3.3.1]-Ph en VCH[3.2.2]-Ph en PA-Ph is suksesvol gesintetiseer en gekarakteriseer met KMR en IR spektroskopie. Die kristalstrukture van [Rh(acac)(CO)(4R, 8S-Lim-Ph)] en [Rh(acac)(CO)(PA-Ph)] is verkry en gekarakteriseer met X-straal kristallografie. Die oksidatiewe addisie en CO-inlassings reaksies van die rhodium komplekse van die ligande is uitgevoer en die resultate dui aan dat die Lim-Ph sisteem die meeste aktief was van al die bisikliese ligande wat ingesluit is in die studie. Die algemene reaktiwiteits reeks vir die oksidatiewe addisie is bepaal as: 4S, B8S-Lim-Ph > 4R, 8S-Lim-Ph > VCH-Ph > Phoban[3.3.1]-Ph > Phoban[4.2.1]-Ph> PPh3 - PCy3 >PA-Ph. Die totale reaktiwiteits orde vir die CO-inlassings reaksie is bepaal as 4S, 8SLim- Ph > 4R, 8S-Lim-Ph > Phoban[4.2.1]-Ph > VCH-Ph > Phoban[3.3.1]-Ph > PA-Ph.
Thesis (Ph.D. (Chemistry))--University of the Free State, 2010
Keywords: Catalysis; Cobalt; Hydroformylation; Autoclave; Crystallography; Phosphine ligands; Selenide complexes; Coupling constant; Rhodium; Oxidative addition; CO-insertion; UV/vis; Infra Red; Stopped flow; Kinetics; Phosphine; Ligands; Phosphorus compounds